Effects of a single dose of captopril on blood pressure and the renin-angiotensin-aldosterone system in normal subjects and hypertensive patients with various etiologies - Kumahara, Yuichi; Higaki, Jitsuo; Maruyama, Anna; Takeshi, Hata; Mikami, Hiroshi; Naka, Toru; Ogihara, Toshio; Kanda, Takao; Gotoh, Motoki (Nihon Jinzo Gakkai shi, 1979)
Effect of a single dose of captopril on blood pressure and the renin-angiotensin-aldosterone (R-A-A) system was evaluated in 0 normal subjects and 11 hypertensive patients with various etiologies. Captopril was administered orally to normal healthy subjects and hypertensive patients on unrestricted diet. Blood pressure was monitored for 4 hours. Blood was drawn at 0, 30 min., 1, 2, 3 and 4 hours for analysis of plasma renin activity (PRA), angiotensin I concentration (AI) and aldosterone concentration (PAC). Angiotensin II analogue (AIIA) test was done in each sub-jects after sodium depletion (40 mg f urosemide administration daily and mild sodium restricted diet for 3 days) Captopril in a dose of 100 mg caused no blood pressure change, increased PRA, AI and decreased PAC in normal subjects. When captopril was administered to patients with renovascular or malig-nant hypertension, blood pressure fell significantly for 4 hours, PRA and Al increased and PAC decreased for 4 hours. In low reninemic patients these paramenters showed little change. In all the subjects studied, change in mean blood pressure was inversely correlated with pre-treatment PRA value (y=-1.4×-2.8, r=0.85, p>0.001). Magnitude of blood pressure reduction by captopril was significantly correlated with that induced by angiotensin II antagonist (y=0.8×-5.0, r=0.93, p>0.001). From the results obtained, it is concluded that the acute blood pressure lowering effect of captopril in hyperreninemic hypertensive patients closely related to its effect on the suppression of R-A-A system. It may be useful to monitor the acute phase response of captopril to provide a prediction for the effectiveness of long term treatment of hypertension.